Evaluation of relation between styles of conflict management and creativity of staff in teaching hospitals of Kerman city in 2008 - Mahmoud Nekuei Moghaddam; Azadeh Taghavi Rad; Saeedeh Hakimipour; Milad Shafiei; Gholamreza Goudarzi (Tehran University of Medical Sciences, 2011)
Background: The world is changing continually and organizations as the subsystems of the world should be adapted with these changes by helping to develope of creativity and innovation.This study to evaluate the relationships between conflict management styles and creativity of staff in training hospitals in  Kerman province. Materials & Methods:This is a cross-sectional study from aspect of descriptive -analytical. For gathering data, the standard questionnaires of conflict management for managers and creativity for staff applied. The participants in the study were all disciplinary managers from selected hospitals in one group and all disciplinary staff of selected hospitals in another group.Data analysis used in SPSS software. Results:The results showed that there is a significant and opposite assosiation between enforcing styles and negotiating styles between managers (P<0/05, r= -0/187) and creativity of staff (P<0/05 , r= -0/155) . Meanwhile, there is a significant relation between marital status and educated staff and their creativity. This research reveales that avoiding styles applied among men is less than women. Conclusion: To develop creativity of staff and managers should decrease using of enforcing and negotiating styles to solve the conflicts in hospitals.